Fatigue Resistance and Cracking Mechanism of Concrete Pavements Reinforced with Recycled Steel Fibres Recovered from Post-consumer Tyres - Graeff, Angela Gaio; Pilakoutas, Kypros; Neocleous, Kyriacos; Peres, Maria Vania N.N. (My University, 2012)
Recycled steel fibres recovered from post-consumer tyres can be used as reinforcement in concrete to enhance its post-cracking flexural behaviour and may also improve its fatigue behaviour. This paper aims to examine the use of recycled steel fibres as fatigue reinforcement for concrete pavements, based on an experimental investigation. Concrete prisms were subjected to cyclic third-point flexural loads at a frequency of 15. Hz, at maximum stress levels of 0.5, 0.7 and 0.9. Two types of mixes, conventional and roller compacted concrete, and two recycled fibre contents, 2% and 6% by mass of concrete were used. Unreinforced and industrially produced fibre reinforced concrete mixes were also tested for comparison purposes. The recycled fibres were found to improve the fatigue behaviour of concrete, especially for conventional plastic concrete mixes. Recycled fibres improve fatigue by restraining the propagation of micro-cracks into meso and macro-cracks, whilst industrially produced fibres are more efficient at arresting macro-cracks. For enhanced fatigue performance, it is recommended that recycled fibres should be used in combination with industrially produced fibres. Predictive models are developed using a probabilistic approach. The results show that the use of recycled steel fibres may contribute to a reduction of up to 26% of pavement thickness, when considering the influence of fatigue alone. © 2012 Elsevier Ltd.
Keywords: Concrete; Fatigue; Pavement; Recycling; Roller-compacted; Steel fibres; Tyres